The character inetto in Una vita, by Italo Svevo - Castelan, Ivair Carlos [UNESP] (Univ Estadual Paulista-unesp, 2016)
The presence of the character inetto (literally the unfit) is one of the main themes of the literary work of the Italian writer Italo Svevo. Svevo's protagonists are marked by inertia, by apathy towards life. In this work, we intend to highlight in the debut novel of Svevo, Una vita, published in 1892, how the depiction of the inetto is represented by the protagonist Alfonso Nitti. Although Mr. Nitti has characteristics which define him as an inept in front of his reality, we intend to demonstrate that in certain situations he considereably distances himself from the archetypal inetto. We will see that Alfonso Nitti is a regular subject, a representative of the modern subject that has qualities and flaws, strengths and weaknesses.
Keywords: Italo Svevo; Una vita; Inetto; Italian literature